The Correlations Between Concentrations of Myeloperoxidase, Serum Amyloid-A Protein and Scretory Phospolipase A-2 with Proinflammatory HDL in Healthy Male Person - Marita Kaniawati; Andi Wijaya; Anwar Susanto (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Low-HDL cholesterol is a risk factor of CAD. Although levels of HDLC are within normal limit in some patients, they suffer CAD. These normal HDL-C levels might become pro-inflammatoric. This study is to measure the correlations between myeloperoxidase (MPO), serum amyloid-A (SAA) protein, and secretoryphospholipase-A2 (sPLA2) with inflammatory status of HDL-C.METHODS: This was a cross-sectional study recruited 49 subjects with high HDL-C (> 40 mg/dL) and 31 subjects with low HDL-C (< 40 mg/dL). HDL-C was determined into antiinflammatory and proinflammatory based on levels of Apo A-1 and hs-CRP. Concentrations of MPO, SAA and s-PLA2 were measured by ELISA method. Levels of Apo A-1 was determined by immunoturbidimetric method. Multiple logistic regression analysis was done using inflammatory status of HDL-C as dependent variables and levels of MPO, SAA, sPLA2, ages, total cholesterol and triglycerides as independent variables.RESULTS: Patient’s age was 43.4 + 8.3 year, HDL-C was 43.1 + 9.5 mg/dL, Apo A-1 was 128.3 + 21.5 mg/dL, hs-CRP was 1.92 + 3.0 mg/dL. Concentrations of MPO, SAA and sPLA2 successively were 63.2 + 16.9 ng/mL, 7015.6 + 5021.1 ng/mL and 1340.2 + 406.3 pg/mL. Multiple logistic regression analysis showed that SAA is an independent predictor of pro-inflammatory status of HDL-C in high HDL-C group with prevalence ratio of 11.74 (95% CI : 2.51 – 54.84; P = 0.002). In contrast, MPO and sPLA2 were not independent predictor with PR of 1.26 (95% CI : 0.30 – 5.23; P = 0.75) and of 0.94 (95% CI : 0.23 – 3.91; P = 0.93).CONCLUSIONS: SAA is an independent predictor of pro-inflammatory HDL-C even in subjects with high HDL-C.KEYWORDS: Atherosclerosis, Apo A-I, serum amyloid A protein, secretory phospholipase A2, myeloperoxidase